The emerging role of m6A methylation in prostate-related diseases: mechanisms and clinical implications - Xie, Qinghua; Zhao, Hongyan; Yang, Xuan; Zhang, Hongqi; Liu, Hong; Pan, Jinghua; Li, Yan; Fan, Danping; Fan, Xinrong (Frontiers in Immunology, 2026)
Prostate-related diseases, including prostatitis, benign prostatic hyperplasia (BPH), and prostate cancer (PCa), represent significant threats to the health of the aging male population worldwide. Despite their prevalence, the pathogenesis of prostate-related diseases has not been elucidated. Recent studies have shown that N6-methyladenosine (m6A) modification is widely involved in the progression of prostate-related diseases. In this review, we summarized recent advances in understanding the core m6A regulatory machinery comprising writers such as the methyltransferase-like 3 (METTL3)-METTL14 complex, erasers including fat mass and obesity-associated protein (FTO) and AlkB homolog 5 (ALKBH5), and readers, including the YTH domain-containing family proteins (YTHDFs), YTHDC proteins, insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs), and heterogeneous nuclear ribonucleoproteins (HNRNPs). Specifically, we elucidated how dysregulation of these components drives disease progression via alterations in cellular proliferation, differentiation, inflammatory responses, and stem cell dynamics. Notably, m6A modifications help shape the immunosuppressive landscape in PCa by modulating immune checkpoint expression, cytokine networks, and immune cell infiltration, thereby critically influencing therapeutic responses to immunotherapy. Furthermore, this review highlights the emerging diagnostic potential and therapeutic viability of m6A-targeted strategies, offering valuable insights for future clinical translation in prostate-related diseases.